Results of geophysical methods of new technology in Andalisia, Spain (2008)
The work is experience of the implementation of geophysical methods with eqipment of digital technology advanced, which were applied in the southeast Spain in the region of Andalusia, Polygon practices of the Technical Institute for Cooperation in the Netherlands (ITCH).  Implemented the resistivity methods ()D resistivity Imagingn), Induced Polarization (I.P.) and the electromagnetic in time domain (TDEM), obtaining cuts representative and analysis of hydrogeological area. Aerial photos and satellite images are handled with the software IL WIS.  The resukts are expressed through longitudinal profiles as pseudocortes od resistivity and polarizabilidada for each techique. The analysis and interpretation of results obtained with the information from aerial photo, identified geological structures in the area "Carboneras", noting alignments related.